OPTIMALISASI UKURAN MANIPULABILITAS ROBOT STANFORD MENGGUNAKAN METODE PSEUDO-INVERSE - admin, Gina Fahrina . (Faculty of Engineering, Universitas Tanjungpura, 2013)
Robot is one of the most important element in the industrial world which has been growing very rapidly. Stanford robot arm is one of robot that use in industry, it has five degrees of freedom (DOF). Movement of the robot arm in his workspace called manipulability or manipulability measure. More the optimal manipulability measure manipulator, the more movement of the robotic arm will be more flexible in his workspace. The purpose of this research are to get knowledge and learn how to solve inverse kinematics using the Pseudo-Inverse at Stanford robot and to compare the characteristic of redundant and nonredundant manipulability measure optimization at Stanford robot arm. This simulations are used to determine manipulability measure optimization by using Matlab 7.6 software. This research produced that the maximum value of the redundancy manipulabilty measure is 7,391, while the value manipulability measure without redundancy was only 4,207. Simulations with redundancy manipulability measure value is high than the value of manipulability measure without redundancy. It means that manipulability measure at Stanford robot that use the redundancy is more optimal than the Stanford robot that does not use redundancy. Thus proved that for optimize manipulability measure is use redundancy. Keywords: degree of freedom, manipulability measure, pseudo-inverse, optimization, redundancy